PENINGKATAN PENDAPATAN MELALUI USAHA EKONOMI KREATIF MELALUI PEMBUATAN SOUVENIR DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Erti, Lili; Murnawati, Murnawati; Tasril, Tasril; Charoline, Santa; Nisa, Putri Hervira (Komunitas Manajemen Kompetitif, 2024)
Community service is a process of educating the community with the aim of improving people's lives or the surrounding environment. Currently, community empowerment activities were also an effort to improve sustainable development. In addition, women in Pandau Jaya Subdistrict, Siak Hulu district generally still have a lot of free time after they finished doing routine household chores. The skills would be improved through community service activities, where they have produced empek-empek ikan patin as cullinary business. Community service activities, which are one of the university's tri dharma activities, it was hoped that it could provided some solutions to help improve knowledge to the community, especially the women of Pandau Jaya subdistrict, Kampar. One of the efforts was increased the creativity and skills of these women, which was to improve the skills of souvenirs. After the process of produced souvenirs, the following steps were to increase the value of products. The target to be achieved through this activity was increasing the skills of mothers to make souvenirs as well as opportunities to develop an entrepreneurial spirit that had been economic value. Keywords: Souvenirs, economic creative, entrepreneurs